Reinforcing film, method for manufacturing device, and reinforcing method

By using acrylic-based polymer with crosslinked structures and photocuring agents in the adhesive layer of the reinforcement film, the problem of the adhesive layer peeling off when the temperature changes in the existing reinforcement film is solved, and high adhesion and resistance are achieved Improved temperature performance.

CN119463727APending Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411089863.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-10
Filing Date
2024-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing reinforcement films tend to cause device warping and adhesive layer peeling when temperature changes, making it difficult to maintain high adhesive force.

Method used

The photocurable adhesive layer containing an acrylic base polymer having a crosslinked structure, a photocuring agent and a photopolymerization initiator is used to increase the adhesion to the adherend by photocuring, and is introduced into the adhesive layer. Crosslinked structures to enhance adhesion and temperature resistance.

Benefits of technology

It is achieved that device warping and adhesive layer peeling are not easily caused under temperature changes, maintaining high adhesion and improving adhesive reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463727A_ABST
    Figure CN119463727A_ABST
Patent Text Reader

Abstract

Provided are a reinforcing film (10), a method for manufacturing a device, and a reinforcing method, the reinforcing film (10) comprising, on one main surface of a film substrate (1), an adhesive layer (2) formed from a photocurable composition containing an acrylic base polymer having a cross-linked structure, a photocuring agent, and a photopolymerization initiator, the photocuring composition contains a polyfunctional (meth) acrylate that does not have a urethane bond and a urethane (meth) acrylate as photocuring agents. The acrylic base polymer contains, as monomer components, a C6-9 alkyl (meth) acrylate, a C10-20 alkyl (meth) acrylate, and at least one selected from the group consisting of a hydroxyl group-containing monomer and a carboxyl group-containing monomer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a reinforcement film formed by fixing and laminating a film substrate and a photocurable adhesive layer. Furthermore, the present invention relates to a method for manufacturing a device having a reinforcement film attached to a surface, and a reinforcement method for fixing and laminating a reinforcement film on the surface of an adherend. Background Art

[0002] An adhesive film is sometimes attached to the surface of an optical device such as a display or an electronic device for the purpose of surface protection, impact resistance, etc. Such an adhesive film usually has an adhesive layer fixedly laminated on the main surface of a film substrate and is attached to the device surface via the adhesive layer.

[0003] By temporarily attaching an adhesive film to the surface of a device or a component of the device before use, such as during assembly, processing, or transportation of the device, damage or breakage of the adherend can be suppressed. Patent document 1 discloses a reinforcement film having a photocurable adhesive layer on a film substrate that includes an acrylic base polymer, a multifunctional (meth)acrylate as a photocuring agent, and a photopolymerization initiator.

[0004] The enhancement film has low adhesion immediately after being attached to the adherend, so it is easy to peel off from the adherend. Therefore, it can be reprocessed from the adherend, and the enhancement film can also be selectively peeled off from the position where the reinforcement of the adherend is not required. The adhesive of the enhancement film is firmly bonded to the adherend by light curing, so that the film substrate is permanently bonded to the surface of the adherend, and can be used as a reinforcement material for surface protection of devices.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2022 / 050009 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The reinforcing film attached to the surface of the device is required to have high adhesion after the adhesive layer is photocured, and not to peel off from the adherend even when the device is deformed or the temperature changes. Patent Document 1 states that by using an acrylic polymer with a low glass transition temperature as a base polymer constituting a photocurable adhesive, the adhesive layer has a low storage elastic modulus and high stress-strain relaxation, thereby suppressing peeling of the adhesive layer at the bent portion of the device and achieving excellent bonding reliability.

[0010] However, when the reinforcing film disclosed in Patent Document 1 is attached to a flexible device using a film substrate and a temperature cycle test is performed in which the temperature is changed from low temperature to high temperature and from high temperature to low temperature, the device may warp or the reinforcing film may peel off. In view of the above problems, an object of the present invention is to provide a reinforcing film that is unlikely to cause warping of an adherend or peeling of the reinforcing film from the adherend even when the temperature is repeatedly changed from low temperature to high temperature.

[0011] Solutions for solving problems

[0012] The reinforcement film of the present invention comprises an adhesive layer fixedly laminated on one main surface of a film substrate. The adhesive layer is formed of a photocurable composition containing an acrylic base polymer having a crosslinked structure, a photocuring agent, and a photopolymerization initiator.

[0013] The acrylic base polymer comprises a (meth)acrylic acid having an alkyl group with 6 to 9 carbon atoms. 6-9 Alkyl esters, (meth)acrylic acid C wherein the alkyl group has 10 to 20 carbon atoms 10-20 The monomer components are selected from the group consisting of an alkyl ester, a hydroxyl group-containing monomer, and a carboxyl group-containing monomer. 6-9 The amount of the alkyl ester is 40 parts by weight or more. 10-20 The amount of the alkyl ester may be 1 to 40 parts by weight.

[0014] A crosslinking structure is introduced into the acrylic base polymer. The crosslinking structure is introduced preferably by using 0.05 to 1.0 parts by weight of a crosslinking agent relative to 100 parts by weight of the polymer. Examples of the crosslinking agent include isocyanate crosslinking agents and epoxy crosslinking agents.

[0015] The photocurable composition constituting the adhesive layer contains a polyfunctional (meth)acrylate having no urethane bond and a urethane (meth)acrylate as a photocuring agent. The amount of the polyfunctional (meth)acrylate having no urethane bond is preferably 2 to 25 parts by weight relative to 100 parts by weight of the acrylic base polymer. The amount of the urethane (meth)acrylate is preferably 0.03 to 5 parts by weight relative to 100 parts by weight of the acrylic base polymer.

[0016] The functional group equivalent of the (meth)acryloyl group of the polyfunctional (meth)acrylate without a urethane bond may be 80 to 500 g / eq. The functional group equivalent of the (meth)acryloyl group of the urethane (meth)acrylate may be 80 to 5000 g / eq. The urethane (meth)acrylate may have 4 or more (meth)acryloyl groups in one molecule.

[0017] The adhesive force F0 of the adhesive layer to the polyimide film at a temperature of 25°C before photocuring is preferably 0.6 N / 25 mm or less. Preferably, the adhesive force F1 of the adhesive layer to the polyimide film at a temperature of 25°C after photocuring is 3.0 N / 25 mm or more, and the adhesive force F2 at a temperature of 85°C is 1.0 N / 25 mm or more.

[0018] The pressure-sensitive adhesive layer after photocuring has a shear storage elastic modulus of 100 kPa or less at a temperature of 25° C. and a shear storage elastic modulus of 1000 kPa or less at a temperature of −40° C.

[0019] After the enhancement film is attached to the surface of the adherend and temporarily fixed, the adhesive layer is photocured to obtain a device with an enhancement film. The device can be a bendable flexible device, and the adherend of the enhancement film (enhancement object) can be a bendable image display element.

[0020] After temporarily fixing the reinforcement film to the adherend and before photocuring the adhesive layer, the reinforcement film temporarily fixed to the adherend may be cut to peel and remove the reinforcement film from a partial region (non-reinforcement target region) on the adherend.

[0021] Effects of the Invention

[0022] The adhesive layer of the reinforcement film of the present invention is formed of a photocurable composition. By photocuring the adhesive layer after bonding to the adherend, the adhesive strength to the adherend is increased. The adhesive layer has a low adhesive strength to the adherend before photocuring and is easily peeled off from the adherend. The adhesive after photocuring has high adhesive strength even at high temperatures, and the change in shear storage elastic modulus with temperature change is small. Therefore, even in the case of repeated temperature changes between low and high temperatures, it is not easy to cause warping of the adherend and peeling of the reinforcement film from the adherend. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a cross-sectional view showing the stacked structure of the reinforcement film.

[0024] Figure 2 It is a cross-sectional view showing the stacked structure of the reinforcement film.

[0025] Figure 3 It is a cross-sectional view showing a device to which a reinforcing film is attached.

[0026] Description of Reference Numerals

[0027] 1: film substrate; 2: adhesive layer; 10: reinforcing film; 5: release liner; 20: adherend. DETAILED DESCRIPTION

[0028] Figure 11 is a cross-sectional view showing an embodiment of a reinforcement film. The reinforcement film 10 includes an adhesive layer 2 on one main surface of a film substrate 1. The adhesive layer 2 is fixedly laminated on one main surface of the film substrate 1. The adhesive layer 2 is a photocurable adhesive formed of a photocurable composition, and is cured by irradiation with active light such as ultraviolet rays, thereby increasing the adhesive strength with the adherend.

[0029] Figure 2 It is a cross-sectional view of a reinforcing film in which a release liner 5 is temporarily fixed to the main surface of the pressure-sensitive adhesive layer 2 . Figure 3 It is a cross-sectional view showing a state where the reinforcing film 10 is attached to the surface of the device 20 .

[0030] The release liner 5 is peeled off from the surface of the adhesive layer 2, and the exposed surface of the adhesive layer 2 is attached to the surface of the device 20, thereby attaching the reinforcement film 10 to the surface of the device 20. In this state, the adhesive layer 2 is before photocuring, and is in a state where the reinforcement film 10 (adhesive layer 2) is temporarily fixed to the device 20. By photocuring the adhesive layer 2, the adhesive force at the interface between the device 20 and the adhesive layer 2 increases, and the device 20 and the reinforcement film 10 are fixed.

[0031] “Anchored” means that two stacked layers are firmly bonded and peeling at the interface between them is impossible or difficult. “Temporary anchored” means that the adhesive force between two stacked layers is weak and peeling at the interface between them is easy.

[0032] Figure 2 In the reinforcement film shown, the film substrate 1 is fixed to the adhesive layer 2, and the release liner 5 is temporarily fixed to the adhesive layer 2. When the film substrate 1 and the release liner 5 are peeled off, peeling occurs at the interface between the adhesive layer 2 and the release liner 5, and the adhesive layer 2 is maintained fixed to the film substrate 1. No adhesive remains on the release liner 5 after peeling.

[0033] Figure 3 In the device with the reinforcement film 10 attached, the device 20 and the adhesive layer 2 are temporarily fixed before the photocuring of the adhesive layer 2. When the film substrate 1 is peeled off from the device 20, peeling occurs at the interface between the adhesive layer 2 and the device 20, and the adhesive layer 2 is kept fixed to the film substrate 1. Since no adhesive remains on the device 20, it is easy to reprocess. After the adhesive layer 2 is photocured, the adhesive force between the adhesive layer 2 and the device 20 increases, so it is difficult to peel the reinforcement film 10 from the device 20. When the two are peeled off, the cohesive failure of the adhesive layer 2 sometimes occurs.

[0034] [Constitution of the reinforcement film]

[0035] <Film base material>

[0036] A plastic film is used as the film substrate 1. In order to fix the film substrate 1 and the adhesive layer 2, it is preferred that the surface of the film substrate 1 on which the adhesive layer 2 is to be attached is not subjected to a release treatment.

[0037] The thickness of the film substrate 1 is, for example, about 4 to 500 μm. From the viewpoint of strengthening the device by imparting rigidity, mitigating impact, etc., the thickness of the film substrate 1 is preferably 12 μm or more, more preferably 30 μm or more, and further preferably 45 μm or more. From the viewpoint of making the reinforcing film flexible and improving operability, the thickness of the film substrate 1 is preferably 300 μm or less, more preferably 200 μm or less. In order to make the reinforcing film flexible and foldable, the thickness of the film substrate 1 is preferably 125 μm or less, more preferably 100 μm or less. From the viewpoint of taking into account both mechanical strength and flexibility, the compressive strength of the film substrate 1 is preferably 100 to 3000 kg / cm 2 , more preferably 200 to 2900 kg / cm 2 , more preferably 300 to 2800 kg / cm 2 , particularly preferably 400 to 2700 kg / cm 2 .

[0038] As the plastic material constituting the film substrate 1, polyester resins, polyolefin resins, cyclic polyolefin resins, polyamide resins, polyimide resins, polyetheretherketone resins, etc. can be cited. In the enhanced film for optical devices such as displays, the film substrate 1 is preferably a transparent film. In addition, in the case where the adhesive layer 2 is photocured by irradiating active light from the film substrate 1 side, the film substrate 1 preferably has transparency for the active light used in the curing of the adhesive layer. Considering both mechanical strength and transparency, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferably used. In the case where the adhesive layer is cured by irradiating active light from the adherend side, as long as the adherend has transparency to the active light, the film substrate 1 may also be opaque to the active light.

[0039] Functional coatings such as an easy-adhesion layer, an easy-slip layer, a release layer, an antistatic layer, a hard coating layer, and an antireflection layer may be provided on the surface of the film substrate 1. It should be noted that, as described above, in order to fix the film substrate 1 and the adhesive layer 2, it is preferred that a release layer is not provided on the surface of the film substrate 1 to which the adhesive layer 2 is attached.

[0040] <Adhesive layer>

[0041] The adhesive layer 2 fixedly laminated on the film substrate 1 is formed of a photocurable composition comprising a base polymer, a photocuring agent, and a photopolymerization initiator. The adhesive layer 2 has a small adhesive force to adherends such as devices and device components before photocuring, so it is easy to peel off. The adhesive layer 2 has an improved adhesive force to the adherend by photocuring, so even when the device is used, the reinforcing film is not easy to peel off from the device surface, and the bonding reliability is excellent.

[0042] Photocurable adhesives hardly cure under normal storage conditions, but cure by irradiation with active light such as ultraviolet rays. Therefore, the reinforcing film of the present invention has the advantages of being able to arbitrarily set the curing timing of the adhesive layer 2 and being able to flexibly cope with the lead time of the process.

[0043] The thickness of the adhesive layer 2 is, for example, about 1 to 300 μm. There is a tendency that the greater the thickness of the adhesive layer 2, the higher the adhesion to the adherend. On the other hand, when the thickness of the adhesive layer 2 is too large, the fluidity before photocuring is sometimes high, and handling becomes difficult. Therefore, the thickness of the adhesive layer 2 is preferably 3 to 100 μm, more preferably 5 to 50 μm, further preferably 6 to 40 μm, and particularly preferably 8 to 30 μm. From the viewpoint of thinning, the thickness of the adhesive layer 2 can be less than 25 μm, less than 20 μm, or less than 18 μm.

[0044] When the reinforcing film is used in an optical device such as a display, the total light transmittance of the adhesive layer 2 is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The haze of the adhesive layer 2 is preferably 2% or less, more preferably 1% or less, further preferably 0.7% or less, and particularly preferably 0.5% or less.

[0045] Hereinafter, preferred embodiments of the respective components of the photocurable composition constituting the pressure-sensitive adhesive layer 2 will be described in order.

[0046] (Base polymer)

[0047] The base polymer is the main constituent of the adhesive composition and is the main factor that determines the adhesive strength of the adhesive layer. The adhesive composition contains an acrylic polymer as the base polymer. Preferably, more than 50% by weight of the adhesive composition is an acrylic polymer. The acrylic base polymer has excellent optical transparency and adhesion, and the adhesive strength is easy to control.

[0048] As the acrylic polymer, it is preferable to use an acrylic polymer containing an alkyl (meth)acrylate as a main monomer component. In addition, in this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0049] As the alkyl (meth)acrylate, preferably one having an alkyl group with carbon atoms of 1 to 20. The alkyl (meth)acrylate may have a branched alkyl group or a cyclic alkyl group (alicyclic alkyl group).

[0050] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.

[0051] Specific examples of the alkyl (meth)acrylate having an alicyclic alkyl group include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate and the like; (meth)acrylate having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; (meth)acrylate having a tricyclic or higher aliphatic hydrocarbon ring such as tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate. The alkyl (meth)acrylate having an alicyclic alkyl group may be an alkyl (meth)acrylate having a substituent on the ring such as 3,3,5-trimethylcyclohexyl (meth)acrylate. Furthermore, the (meth)acrylate alkyl ester having an alicyclic alkyl group may be a (meth)acrylate having a condensed ring of an alicyclic structure and a ring structure having an unsaturated bond, such as dicyclopentenyl (meth)acrylate.

[0052] The content of the alkyl (meth)acrylate is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and may be 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more, relative to 100 parts by weight of the total amount of monomer components constituting the polymer.

[0053] From the viewpoint of lowering the glass transition temperature (Tg) of the acrylic base polymer and improving the adhesive strength in a wide temperature range, the alkyl group of the (meth)acrylic acid alkyl ester is preferably a chain alkyl group. The chain alkyl group may be linear or branched.

[0054] In the present invention, the acrylic base polymer comprises (meth)acrylic acid having an alkyl group with 6 to 9 carbon atoms. 6-9 Alkyl esters and (meth) acrylic acid having 10 to 20 carbon atoms in the alkyl group 10-20 Alkyl esters are used as monomer components.

[0055] (Meth) acrylic acid C 6-9 Since the glass transition temperature (Tg) of the homopolymer of alkyl ester is low, the acrylic base polymer is preferably prepared by containing (meth)acrylic acid C 6-9 Alkyl esters are used as monomer components to lower the Tg of acrylic base polymers. From the perspective of lowering Tg, in (meth) acrylic acid C 6-9 Among alkyl esters, the glass transition temperature of the homopolymer is preferably -50°C or lower.

[0056] (Meth)acrylic acid C having a glass transition temperature of -50°C or less as a homopolymer 6-9 Specific examples of the alkyl ester include 2-ethylhexyl acrylate (Tg: -70°C), n-hexyl acrylate (Tg: -65°C), n-octyl acrylate (Tg: -65°C), isononyl acrylate (Tg: -60°C), n-nonyl acrylate (Tg: -58°C), isooctyl acrylate (Tg: -58°C), etc. Among these, 2-ethylhexyl acrylate and n-octyl acrylate are preferred because they have low Tg and can reduce the storage elastic modulus of the adhesive.

[0057] The acrylic base polymer preferably has the largest content of (meth)acrylic acid (main monomer) in the monomers constituting the acrylic base polymer. 6-9 Alkyl ester. Relative to 100 parts by weight of the total amount of the monomer components constituting the polymer, (meth)acrylic acid C 6-9 The amount of the alkyl ester is preferably 40 parts by weight or more, more preferably 50 parts by weight or more, and may be 55 parts by weight or more, 60 parts by weight or more, or 65 parts by weight or more.

[0058] (Meth) acrylic acid C 10-20The homopolymer of the alkyl ester has a temperature region (plateau region) in which the temperature dependence of viscoelasticity is small at a temperature higher than Tg. 10-20 The alkyl ester as a monomer component reduces the temperature dependence of the storage elastic modulus, and may suppress warping of the adherend accompanying temperature changes and peeling of the reinforcement film from the adherend.

[0059] Since the temperature range of the plateau region is wide and the storage elastic modulus in the plateau region is small, the (meth) acrylic acid C 10-20 Among the chain alkyl esters, (meth)acrylic acid C 12-18 Among them, lauryl (meth)acrylate and isostearyl (meth)acrylate are preferred, and lauryl acrylate (lauryl acrylate) is particularly preferred.

[0060] With respect to 100 parts by weight of the total amount of the monomer components constituting the polymer, (meth)acrylic acid C 10-20 The amount of the alkyl ester is preferably 1 to 40 parts by weight, more preferably 2 to 30 parts by weight, further preferably 3 to 25 parts by weight, and may be 4 to 20 parts by weight or 5 to 15 parts by weight.

[0061] The acrylic base polymer may also contain (meth)acrylic acid C 6-9 Alkyl esters and (meth) acrylic acid C 10-20 As the (meth)acrylic acid alkyl ester other than the above-mentioned alkyl ester, (meth)acrylic acid C such as butyl acrylate is preferred. 1-5 Alkyl esters.

[0062] In addition to containing (meth) alkyl acrylate, acrylic acid base polymer also contains hydroxyl-containing monomer and / or carboxyl-containing monomer as a constituent monomer component. The hydroxyl and carboxyl groups of the base polymer become reaction points with the cross-linking agent described later. For example, when using an isocyanate cross-linking agent, as a monomer component of the base polymer, it is preferred to contain a hydroxyl-containing monomer. When using an epoxy cross-linking agent, as a monomer component of the base polymer, it is preferred to contain a carboxyl-containing monomer. By introducing a cross-linked structure in the base polymer, there is a tendency that the cohesive force is improved and the peelability of the adhesive layer 2 before photocuring from the adherend is improved.

[0063] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate. Among these, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are preferred because they contribute greatly to improving the adhesive strength of the adhesive after photocuring.

[0064] Examples of carboxyl group-containing monomers include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred, from the perspective of increasing the cohesiveness of the adhesive and thus easily improving the adhesive force and adhesive retention.

[0065] From the viewpoint of appropriately introducing a cross-linked structure formed by a cross-linking agent such as an isocyanate cross-linking agent or an epoxy cross-linking agent, the total amount of the hydroxyl group-containing monomer and the carboxyl group-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may also be 0.7 parts by weight or more or 1.0 parts by weight or more, relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer.

[0066] Since hydroxyl and carboxyl groups are highly polar, when the amount of hydroxyl-containing monomers and carboxyl-containing monomers in the monomer components constituting the acrylic base polymer is large, there is a tendency that the cohesive force of the polymer becomes high and the storage elastic modulus of the adhesive layer after photocuring becomes large. From the viewpoint of reducing the storage elastic modulus of the adhesive layer 2, the total amount of hydroxyl-containing monomers and carboxyl-containing monomers is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, further preferably 10 parts by weight or less, and may also be 7 parts by weight or less or 5 parts by weight or less, relative to 100 parts by weight of the total amount of the monomer components constituting the acrylic base polymer.

[0067] The acrylic base polymer may contain a nitrogen atom-containing monomer as a constituent monomer component. The nitrogen atom-containing monomer has high polarity, high cohesive force, and a high glass transition temperature of the homopolymer. Therefore, by making the acrylic base polymer contain a nitrogen atom-containing monomer as a monomer component, there is a tendency for the adhesive force of the adhesive layer after photocuring to be improved at a high temperature.

[0068] Examples of nitrogen atom-containing monomers include N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam. Among them, N-vinylpyrrolidone is particularly preferred because of its high cohesive force and its large contribution to improving the adhesive force at high temperatures.

[0069] In the case where the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, from the viewpoint of improving the adhesive strength of the adhesive layer after photocuring at high temperatures, the amount of the nitrogen atom-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more relative to 100 parts by weight of the total amount of the monomer components constituting the polymer. Even a small amount of the nitrogen atom-containing monomer can contribute to improving the adhesive strength at high temperatures.

[0070] When the amount of nitrogen-atom-containing monomers in the monomer components of the acrylic base polymer is large, there is a tendency that the cohesive force of the base polymer is high and the glass transition temperature of the adhesive layer becomes high, and there is a tendency that the storage elastic modulus of the adhesive layer after photocuring becomes large. In addition, when the amount of nitrogen-atom-containing monomers is large, there is a tendency that the adhesive force of the adhesive layer 2 before photocuring is high and the peeling of the reinforcing film from the adherend becomes difficult. From the viewpoint of reducing the adhesive force of the adhesive before photocuring and reducing the storage elastic modulus of the adhesive after photocuring, the amount of nitrogen-atom-containing monomers is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, and may also be 5 parts by weight or less or 3 parts by weight or less, relative to 100 parts by weight of the total amount of the monomer components of the acrylic base polymer.

[0071] The acrylic base polymer may contain monomer components other than those described above. The acrylic base polymer may contain, for example, vinyl ester monomers, aromatic vinyl monomers, epoxy group-containing monomers, vinyl ether monomers, sulfone group-containing monomers, phosphoric acid group-containing monomers, acid anhydride group-containing monomers, etc. as monomer components.

[0072] From the viewpoint of providing the adhesive with excellent adhesiveness, the glass transition temperature of the acrylic base polymer is preferably -30°C or lower, more preferably -40°C or lower, further preferably -50°C or lower, and may be -55°C or lower or -60°C or lower. The glass transition temperature of the acrylic base polymer is usually -100°C or higher, and may be -80°C or higher or -70°C or higher.

[0073] The glass transition temperature (Tg) is the temperature (peak temperature) at which the loss tangent tanδ in the viscoelasticity measurement reaches a maximum. The theoretical glass transition temperature can also be used instead of the glass transition temperature based on the viscoelasticity measurement. The theoretical Tg is the glass transition temperature Tg of the homopolymer of the monomer component constituting the polymer. i and the weight fraction W of each monomer component i Calculated by the following Fox formula.

[0074] 1 / Tg=Σ(W i / Tg i )

[0075] Tg is the theoretical glass transition temperature of the polymer (unit: K), W i is the weight fraction of monomer component i (copolymerization ratio based on weight), Tg i is the glass transition temperature of the homopolymer of monomer component i (unit: K). As the glass transition temperature of the homopolymer, the value described in the third edition of Polymer Handbook (John Wiley & Sons, Inc., 1989) can be used. The glass transition temperature of the homopolymer of a monomer not described in the above literature can be the peak temperature of tan δ measured based on dynamic viscoelasticity.

[0076] The above-mentioned monomer components are polymerized by various known methods such as solution polymerization, emulsion polymerization, and bulk polymerization to obtain an acrylic polymer as a base polymer. From the perspective of the balance of characteristics such as the adhesion and holding power of the adhesive, and the cost, solution polymerization is preferred. As a solvent for solution polymerization, ethyl acetate, toluene, etc. can be used. The solution concentration is usually about 20 to 80% by weight. As a polymerization initiator used in solution polymerization, various known polymerization initiators such as azo and peroxide can be used. In order to adjust the molecular weight, a chain transfer agent can be used. The reaction temperature is usually about 50 to 80°C, and the reaction time is usually about 1 to 8 hours.

[0077] The weight average molecular weight of the acrylic base polymer is preferably 200,000 or more, more preferably 300,000 or more, and further preferably 500,000 or more. The larger the weight average molecular weight of the base polymer, the more there is a tendency for the adhesive force at high temperature to improve. The weight average molecular weight of the acrylic base polymer may be 1,000,000 or more, 1,300,000 or more, 1,500,000 or more, 1,600,000 or more, or 1,700,000 or more.

[0078] When the weight average molecular weight of the base polymer is too large, there is a tendency that the storage elastic modulus of the adhesive is large, and the bonding force and flexibility are reduced. Therefore, the weight average molecular weight of the acrylic base polymer is preferably less than 3,000,000, more preferably less than 2,500,000, and may be less than 2,200,000 or less than 2,000,000. When a cross-linked structure is introduced into the base polymer, the molecular weight of the base polymer refers to the molecular weight before the cross-linked structure is introduced.

[0079] (Crosslinking agent)

[0080] From the viewpoint of making the adhesive have appropriate cohesive force, showing bonding force and ensuring the peelability of the adhesive layer before photocuring from the adherend, it is preferred to introduce a crosslinked structure in the base polymer. For example, a crosslinking agent is added to the solution after the base polymer is polymerized, and heating is performed as required to thereby introduce a crosslinked structure. The crosslinking agent has more than 2 crosslinking functional groups in one molecule. The crosslinking agent can have more than 3 crosslinking functional groups in one molecule.

[0081] As the crosslinking agent, isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, metal chelate crosslinking agents, etc. can be cited. These crosslinking agents react with functional groups such as hydroxyl groups and carboxyl groups introduced into the acrylic base polymer to form a crosslinked structure. From the perspective of high reactivity with hydroxyl groups and carboxyl groups of the acrylic base polymer and easy introduction of a crosslinked structure, isocyanate crosslinking agents and epoxy crosslinking agents are preferred.

[0082] As the isocyanate-based crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule is used. The isocyanate-based crosslinking agent may have three or more isocyanate groups in one molecule. Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adducts (e.g., "TAKENATE D101E" manufactured by Mitsui Chemicals), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., "CORONATE HL" manufactured by Tosoh), trimethylolpropane adducts of xylylene diisocyanate (e.g., "TAKENATE D110N" manufactured by Mitsui Chemicals), isocyanurates of hexamethylene diisocyanate (e.g., "CORONATE 300" manufactured by Tosoh), and isocyanurates of hexamethylene diisocyanate (e.g., "CORONATE 500" manufactured by Tosoh). As the isocyanate crosslinking agent, an isocyanate compound having a biuret group (for example, "DURANATE 24A-100" manufactured by Asahi Chemical Industry Co., Ltd.) or an isocyanate compound having an allophanate group can be used.

[0083] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. The epoxy crosslinking agent can have three or more or four or more epoxy groups in one molecule. The epoxy group of the epoxy crosslinking agent can be a glycidyl group. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase ChemteX, and "TETRAD X" and "TETRAD C" manufactured by Mitsubishi Gas Chemical can be used.

[0084] The amount of crosslinking agent used can be appropriately adjusted according to the composition and molecular weight of the acrylic base polymer, and is preferably about 0.01 to 3 parts by weight relative to 100 parts by weight of the acrylic base polymer. The more the amount of crosslinking agent, the higher the crosslinking density of the base polymer, the greater the storage elastic modulus of the adhesive layer before photocuring, and the tendency of the residual adhesive on the adherend to be suppressed when the reinforcing film is peeled off from the adherend. On the other hand, when the amount of crosslinking agent is too much, there is a tendency for the adhesive force of the adhesive layer after photocuring to decrease, especially the adhesive force at high temperature tends to decrease. In addition, when the amount of crosslinking agent is large, there is a tendency for the storage elastic modulus of the adhesive layer after photocuring to increase at low temperatures, which may become the cause of the warping of the adherend caused by temperature changes and the peeling of the reinforcing film from the adherend. From the viewpoint of achieving both low adhesion (easy peelability) of the adhesive layer before photocuring and high adhesion of the adhesive layer after photocuring, and reducing the storage elastic modulus, the amount of the cross-linking agent is more preferably 0.05 to 1.0 part by weight, further preferably 0.1 to 0.7 part by weight, and may also be 0.15 to 0.6 part by weight, 0.2 to 0.5 part by weight, or 0.25 to 0.4 part by weight, relative to 100 parts by weight of the acrylic base polymer.

[0085] (Light curing agent)

[0086] The adhesive composition constituting the adhesive layer 2 contains, in addition to the base polymer, a compound having two or more photopolymerizable functional groups in one molecule as a photocuring agent. The adhesive composition containing the photocuring agent has photocurability, and when the adhesive composition is attached to an adherend and then photocured, the adhesive strength to the adherend is improved.

[0087] From the viewpoint of compatibility with the base polymer, the photocuring agent is preferably liquid at room temperature. The photopolymerizable functional group of the photocuring agent preferably has polymerizability based on photoradical reaction. As the photocuring agent, a compound having two or more ethylenically unsaturated bonds in one molecule is preferred, and from the viewpoint of showing appropriate compatibility with the acrylic base polymer, a multifunctional (meth) acrylate is preferred.

[0088] In the present invention, as a photocuring agent, a multifunctional (meth) acrylate without a carbamate bond and a multifunctional (meth) acrylate with a carbamate bond are used. That is, the photocurable composition constituting the adhesive layer 2 contains a multifunctional (meth) acrylate without a carbamate bond and a multifunctional (meth) acrylate with a carbamate bond. Hereinafter, the multifunctional (meth) acrylate with a carbamate bond is described as "carbamate (meth) acrylate". In addition, sometimes the multifunctional (meth) acrylate without a carbamate bond is abbreviated as "multifunctional (meth) acrylate".

[0089] Examples of the polyfunctional (meth)acrylate having no urethane bond include compounds having (meth)acryloyl groups at both ends of a polyoxyalkylene chain, such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate; esters of polyols and (meth)acrylic acid, such as bisphenol A di(meth)acrylate, alkanediol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isocyanuric acid tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol poly(meth)acrylate; and epoxy (meth)acrylates.

[0090] The polyfunctional (meth)acrylate having no urethane bond may be an ester of a polyol modified with oxyalkylene and (meth)acrylic acid. Examples of the ester of a polyol modified with oxyalkylene and (meth)acrylic acid include bisphenol A oxyalkylene-modified di(meth)acrylate, isocyanuric acid oxyalkylene-modified tri(meth)acrylate, trimethylolpropane oxyalkylene-modified tri(meth)acrylate, pentaerythritol oxyalkylene-modified di(meth)acrylate, pentaerythritol oxyalkylene-modified tri(meth)acrylate, and dipentaerythritol oxyalkylene-modified poly(meth)acrylate.

[0091] Among the above, from the viewpoint of reducing the adhesive force of the adhesive layer before photocuring to facilitate peeling and improving the adhesive force of the adhesive layer after photocuring, a polyfunctional (meth)acrylate having an oxyalkylene chain is preferred. Examples of the polyfunctional (meth)acrylate having an oxyalkylene chain include compounds having (meth)acryloyl groups at both ends of the polyoxyalkylene chain, such as polyethylene glycol di(meth)acrylate and polypropylene glycol di(meth)acrylate, and esters of polyols modified with oxyalkylene and (meth)acrylic acid.

[0092] In the polyfunctional (meth)acrylate containing an oxyalkylene chain, as the oxyalkylene group, a (poly)oxyethylene group or a (poly)oxypropylene group is preferred, and a (poly)oxyethylene group is particularly preferred. The chain length n of the oxyalkylene group (the number of repeating units of the oxyalkylene group) is about 1 to 15. When a plurality of oxyalkylene chains are contained in one molecule, the preferred average chain length n is 1 to 15. The (average) chain length n of the oxyalkylene chain can be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. By adjusting the type and chain length of the oxyalkylene group, the compatibility with the acrylic base polymer can be adjusted.

[0093] As the oxyalkylene group, (poly)oxyethylene or (poly)oxypropylene is preferred, and the chain length (number of repeating units: n) of the oxyalkylene group is preferably about 1 to 15. When a plurality of oxyalkylene chains are contained in one molecule, the average chain length n is preferably 1 to 15. The (average) chain length n of the oxyalkylene chain may be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. By adjusting the type and chain length of the oxyalkylene group, the compatibility with the acrylic base polymer can be adjusted.

[0094] As the photocuring agent, two or more multifunctional (meth)acrylates without urethane bonds may be used in combination. For example, a multifunctional (meth)acrylate having relatively low compatibility with the acrylic base polymer and a multifunctional (meth)acrylate having relatively high compatibility with the acrylic base polymer may be used in combination. For example, a multifunctional (meth)acrylate without an oxyalkylene chain has high compatibility with the acrylic base polymer compared to a multifunctional (meth)acrylate having an oxyalkylene chain.

[0095] From the viewpoint of compatibility with the acrylic base polymer, the molecular weight of the multifunctional (meth)acrylate as a photocuring agent is preferably 1500 or less, more preferably 1000 or less, and may be 800 or less, 500 or less, or 400 or less. From the viewpoint of achieving both compatibility with the acrylic base polymer and improved adhesive force after photocuring, the functional group equivalent (g / eq) of the multifunctional (meth)acrylate is preferably 500 or less, more preferably 400 or less, further preferably 300 or less, particularly preferably 200 or less, and may be 180 or less or 160 or less.

[0096] On the other hand, if the functional group equivalent of the multifunctional (meth)acrylate is too small, the crosslinking point density of the adhesive layer after photocuring becomes high, and sometimes the adhesion is reduced. Therefore, the functional group equivalent of the multifunctional (meth)acrylate is preferably 80 or more, more preferably 100 or more, and may be 120 or more or 130 or more.

[0097] By including a multifunctional (meth)acrylate having an oxyalkylene chain and a urethane (meth)acrylate as a photocuring agent, there is a tendency for the adhesive force (initial adhesive force) of the adhesive layer before photocuring to become smaller. In addition, by including a urethane (meth)acrylate as a photocuring agent, the adhesive force, especially the adhesive force at high temperature, can be improved without excessively increasing the storage elastic modulus of the adhesive layer after photocuring.

[0098] Urethane (meth) acrylate is a compound having one or more urethane bonds and two or more (meth) acryloyl groups in one molecule, preferably containing two or more urethane bonds in one molecule. Urethane (meth) acrylate having two or more urethane bonds is obtained, for example, by the reaction of a polyisocyanate with a (meth) acrylic compound having a hydroxyl group, and the isocyanate group of the polyisocyanate is bonded to the hydroxyl group of the (meth) acrylic compound to form a urethane bond.

[0099] The polyisocyanate may be any one of an aromatic polyisocyanate, an alicyclic polyisocyanate and an alicyclic polyisocyanate. Among them, aromatic polyisocyanates and aliphatic polyisocyanates are preferred. As the aromatic polyisocyanate, toluene diisocyanate (TDI) is particularly preferred. Toluene diisocyanate may be any one of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, or a mixture of the two. As the aliphatic polyisocyanate, hexamethylene diisocyanate (HDI) is particularly preferred.

[0100] The polyisocyanate may be a trifunctional isocyanate having a cyanuric acid skeleton. Examples of the trifunctional isocyanate having a cyanuric acid skeleton include TDI trimer and HDI trimer. The polyisocyanate may also be a polyisocyanate having a biuret group or an allophanate group.

[0101] The polyisocyanate may be an isocyanate-terminated urethane prepolymer obtained by reacting a polyol with a polyisocyanate. The isocyanate-terminated urethane prepolymer may be a high molecular weight product obtained by reacting a high molecular weight polyol such as polyester polyol, polycarbonate polyol, or polyether polyol with a polyisocyanate.

[0102] Examples of the (meth)acrylic compound having a hydroxyl group include compounds having one hydroxyl group and one (meth)acryloyl group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxymethacrylamide, and hydroxyethylacrylamide; and compounds having one hydroxyl group and two or more (meth)acryloyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, and isocyanuric acid di(meth)acrylate.

[0103] Among them, the (meth)acrylic compound having a hydroxyl group is preferably a compound having one hydroxyl group and two or more (meth)acryloyl groups, and specific examples thereof include compounds having a pentaerythritol skeleton such as pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.

[0104] The urethane (meth) acrylate obtained by the reaction of a diisocyanate with a (meth) acrylic compound having one hydroxyl group and two or more (meth) acryloyl groups in one molecule has two urethane bonds and four or more (meth) acryloyl groups in one molecule. The number of (meth) acryloyl groups in the urethane (meth) acrylate may be 6 or more or 8 or more, or 12 or less or 10 or less.

[0105] As the urethane (meth)acrylate, commercially available products such as those produced by Kyoeisha Chemical, Shin-Nakamura Chemical, Negami Industries, Mitsubishi Chemical, Daicel-Allnex, and Resonac can be used.

[0106] From the viewpoint of compatibility with the acrylic base polymer and adjustment of the adhesive force of the adhesive layer, the molecular weight of the urethane (meth) acrylate is preferably 300 to 10,000, more preferably 500 to 2,000, and may be 600 to 1,500 or 700 to 1,200. From the same viewpoint, the functional group equivalent (g / eq) of the (meth) acryloyl group of the urethane (meth) acrylate is preferably 80 to 5,000, more preferably 90 to 1,000, further preferably 100 to 300, and may be 110 to 250 or 120 to 200.

[0107] The content of the photocuring agent in the adhesive composition (the total of the multifunctional (meth)acrylate without a urethane bond and the urethane (meth)acrylate) is preferably 2 parts by weight or more, more preferably 3 parts by weight or more, further preferably 5 parts by weight or more, and may also be 7 parts by weight or more, 8 parts by weight or more, or 10 parts by weight or more, relative to 100 parts by weight of the acrylic base polymer. By setting the compounding amount of the photocuring agent to the above range, the photocuring agent can be easily peeled off from the adherend before curing, and a reinforcement film that can be firmly bonded to the adherend by photocuring can be obtained.

[0108] The more the amount of photocuring agent, the smaller the adhesive force between the adhesive and the adherend before photocuring, and the better the peeling property. On the other hand, when the amount of photocuring agent is too much, there is a tendency that the viscosity of the adhesive is low, the adhesive force and the flexibility are insufficient. In addition, the more the amount of photocuring agent, the greater the storage elastic modulus of the adhesive layer after photocuring, especially the storage elastic modulus at low temperature, the easier it is to produce the warping of the adherend with the enhanced film and the enhanced film attached with the temperature change. And then, when the amount of photocuring agent is too much, the photocuring agent is easy to ooze out, and when the enhanced film is peeled off from the adherend, the exuded component is sometimes transferred to the adherend and becomes the cause of pollution. Therefore, relative to 100 parts by weight of the base polymer, the content of the photocuring agent is preferably less than 30 parts by weight, more preferably less than 25 parts by weight, and can be less than 20 parts by weight, less than 15 parts by weight, less than 12 parts by weight or less than 10 parts by weight.

[0109] From the viewpoint of adjusting the adhesion between the adhesive layer and the adherend before and after photocuring and the storage elastic modulus of the adhesive layer after photocuring to an appropriate range, the content of the multifunctional (meth)acrylate not having a urethane bond is preferably 2 to 25 parts by weight, more preferably 3 to 20 parts by weight, further preferably 4 to 15 parts by weight, and may also be 5 to 13 parts by weight, 6 to 12 parts by weight, or 7 to 10 parts by weight, relative to 100 parts by weight of the acrylic base polymer.

[0110] From the viewpoint of adjusting the adhesion between the adhesive layer and the adherend before and after photocuring and the storage elastic modulus of the adhesive layer after photocuring to an appropriate range, the content of the urethane (meth) acrylate is preferably 0.03 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, further preferably 0.08 to 3 parts by weight, and may also be 0.1 to 2.5 parts by weight or 0.15 to 2 parts by weight, relative to 100 parts by weight of the acrylic base polymer.

[0111] Urethane (meth)acrylate has low compatibility with acrylic base polymers. Therefore, urethane (meth)acrylate tends to be localized on the surface of the adhesive layer (near the bonding interface with the adherend). In addition, multifunctional (meth)acrylates having an oxyalkylene chain have low compatibility with acrylic base polymers compared to multifunctional (meth)acrylates not having an oxyalkylene chain. These photocuring agents tend to be localized on the surface of the adhesive layer (near the bonding interface with the adherend), and a weak boundary layer (WBL) is easily formed by the photocuring agent localized on the bonding interface with the adherend.

[0112] If WBL is formed, the liquid properties of the surface (bonding interface) become stronger while maintaining the overall properties of the adhesive layer such as the storage elastic modulus, so there is a tendency for the adhesive force to become smaller. Therefore, the adhesive layer before photocuring is easily peeled off from the adherend. When the adhesive layer with WBL is photocured by making the photocuring agent biased near the bonding interface with the adherend, the curing reaction of the photocuring agent is easy to proceed near the bonding interface where the density of the photocuring agent is high, so the cohesive force near the bonding interface is easy to increase, and the adhesive force is easy to increase. In addition, when WBL is formed, there is a tendency to suppress the increase of the storage elastic modulus, which is a main property, in the adhesive after photocuring.

[0113] The inclusion of urethane (meth)acrylate as a photocuring agent tends to reduce the adhesive strength of the adhesive layer before photocuring. One reason for this is believed to be the promotion of WBL formation caused by the combined use of urethane (meth)acrylate and a polyfunctional (meth)acrylate having no urethane bond.

[0114] It is believed that in the adhesive layer after photocuring, the acrylic base polymer having a cross-linked structure and the polymer formed by curing of the photocuring agent form a polymer network, and the cohesive force is improved by the interaction between the polar groups of the acrylic base polymer and the polar groups of the urethane (meth) acrylate, so the adhesive force is improved. In addition, as mentioned above, if photocuring is performed in a state where WBL is formed, the cohesive force near the bonding interface is likely to increase, so it is believed that the adhesive force at the interface and the high-temperature adhesive force are likely to increase.

[0115] (Photopolymerization Initiator)

[0116] The photopolymerization initiator generates active species by irradiation with active light rays, and promotes the curing reaction of the photocuring agent. As the photopolymerization initiator, a photoradical polymerization initiator (photoradical generator) is preferably used.

[0117] As the photo-radical polymerization initiator, a photo-radical polymerization initiator that generates free radicals by irradiating visible light or ultraviolet light having a wavelength shorter than 450 nm is preferred, and examples thereof include hydroxyketones, benzyl dimethyl ketals, aminoketones, acylphosphine oxides, benzophenones, trichloromethyl-containing triazine derivatives, etc. The photo-polymerization initiator may be used alone or in combination of two or more.

[0118] The content of the photopolymerization initiator in the adhesive layer 2 is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, and further preferably 0.03 to 2 parts by weight, relative to 100 parts by weight of the base polymer. The content of the photopolymerization initiator in the adhesive layer 2 is preferably 0.02 to 20 parts by weight, more preferably 0.05 to 10 parts by weight, and further preferably 0.1 to 7 parts by weight, relative to 100 parts by weight of the photocuring agent.

[0119] <Other ingredients>

[0120] As described above, the photocurable adhesive composition constituting the adhesive layer 2 includes an acrylic base polymer, a photocuring agent, and a photopolymerization initiator. The adhesive composition may include components other than these.

[0121] For example, the adhesive composition may contain an oligomer having a lower molecular weight than the base polymer. For example, the adhesive composition may contain an acrylic oligomer having a weight average molecular weight of about 1,000 to 30,000 in addition to the acrylic base polymer.

[0122] In addition to the above-mentioned components, the adhesive composition may also contain additives such as silane coupling agents, tackifiers, crosslinking accelerators, crosslinking retarders, plasticizers, softeners, antioxidants, anti-degradation agents, fillers, colorants, ultraviolet absorbers, surfactants, antistatic agents, etc. within the range that does not impair the characteristics of the present invention.

[0123] As a crosslinking accelerator (crosslinking catalyst), organic metal compounds such as organic metal complexes (chelates), compounds of metals and alkoxy groups, and compounds of metals and acyloxy groups can be listed; as well as tertiary amines, etc. From the perspective of suppressing the crosslinking reaction in a solution state at room temperature and ensuring the shelf life of the adhesive composition, organic metal compounds are preferred. In addition, from the perspective of easily introducing a uniform crosslinked structure as a whole in the thickness direction of the adhesive layer, as a crosslinking accelerator, an organic metal compound that is liquid at room temperature is preferred. As metals of the organic metal compound, iron, tin, aluminum, zirconium, zinc, titanium, lead, cobalt, zinc, etc. can be listed.

[0124] Examples of the crosslinking retarder include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate; β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone; and alcohols such as tert-butyl alcohol.

[0125] [Production of reinforcement film]

[0126] A reinforced film can be obtained by laminating the photocurable adhesive layer 2 on the film substrate 1. The adhesive layer 2 may be directly formed on the film substrate 1, or an adhesive layer formed in a sheet form on another substrate may be transferred to the film substrate 1.

[0127] The above-mentioned adhesive composition is applied to the substrate by roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, curtain coating, lip coating, die coating, etc., and the solvent is dried and removed as needed to form an adhesive layer. As a drying method, an appropriate method can be appropriately adopted. The heating and drying temperature is preferably 40 to 200 ° C, more preferably 50 to 180 ° C, and more preferably 70 to 170 ° C. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and more preferably 10 seconds to 10 minutes.

[0128] When the adhesive composition contains a crosslinking agent, it is preferred to crosslink by heating or aging while or after the solvent is dried. The heating temperature and heating time are appropriately set according to the type of crosslinking agent used, and crosslinking is usually carried out by heating at a range of 20 to 160° C. for 1 minute to 7 days. The heating for drying and removing the solvent can also serve as the heating for crosslinking.

[0129] After the crosslinking structure is introduced into the polymer by the crosslinking agent, the photocuring agent also remains in an unreacted state. Therefore, the adhesive layer 2 is formed of a photocurable adhesive composition containing an acrylic base polymer having a crosslinking structure introduced therein, a photocuring agent, and a photopolymerization initiator. When the adhesive layer 2 is formed on the film substrate 1, a release liner 5 is preferably provided on the adhesive layer 2 for the purpose of protecting the adhesive layer 2. Crosslinking can be performed after the release liner 5 is provided on the adhesive layer 2.

[0130] When the pressure-sensitive adhesive layer 2 is formed on another substrate, the reinforced film is obtained by transferring the pressure-sensitive adhesive layer 2 onto the film substrate 1 after drying the solvent. The substrate used for forming the pressure-sensitive adhesive layer may be used as the release liner 5 as it is.

[0131] As the release liner 5, a plastic film such as polyethylene, polypropylene, polyethylene terephthalate, polyester film, etc. is preferably used. The thickness of the release liner is usually 3 to 200 μm, preferably about 10 to 100 μm. It is preferred that the contact surface of the release liner 5 with the adhesive layer 2 is subjected to a release treatment using a release agent such as a silicon-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent or silica powder. By subjecting the surface of the release liner 5 to a release treatment, when the film substrate 1 and the release liner 5 are peeled off, peeling occurs at the interface between the adhesive layer 2 and the release liner 5, and the state in which the adhesive layer 2 is fixed to the film substrate 1 is maintained. The release liner 5 can be subjected to an antistatic treatment on either or both of the release-treated surface and the non-treated surface. By subjecting the release liner 5 to an antistatic treatment, the charge when the release liner is peeled off from the adhesive layer can be suppressed.

[0132] [Reinforcement film characteristics and use of reinforcement film]

[0133] The reinforcing film of the present invention is used by being attached to a device or a component of the device. The adhesive layer 2 of the reinforcing film 10 is fixed to the film substrate 1, and the adhesive force to the adherend is small before being photocured after being attached to the adherend. Therefore, the reinforcing film is easily peeled off from the adherend before photocuring.

[0134] The adherend to which the reinforcement film is bonded is not particularly limited, and various electronic devices, optical devices and their constituent components can be listed. In one embodiment, the reinforcement film is bonded to the surface of a bendable flexible device. The bendable device has a hinge portion and can be bent with the hinge portion as the center. The bending angle can be set arbitrarily, and it can also be bent (folded) 180°. In the case where the device is a display device, the reinforcement film can be bonded to the surface of the screen side, and the reinforcement film can also be bonded to the back side (housing). In a flexible device that is bendable at a specified position such as a hinge portion, bending and stretching are repeatedly performed at the same position when it is in use.

[0135] The enhancement film can be attached to the entire surface of the adherend, or it can be selectively attached only to the part that needs to be enhanced (enhancement target area). After the enhancement film is attached to the entire part that needs to be enhanced (enhancement target area) and the area that does not need to be enhanced (non-enhancement target area), the enhancement film is cut off and the enhancement film is peeled off from the non-enhancement target area, thereby making a device with the enhancement film attached only to the enhancement target area. If the adhesive is before light curing, the enhancement film is temporarily fixed to the surface of the adherend, and the adhesive force is small, so the enhancement film can be easily peeled off from the surface of the adherend.

[0136] By laminating the reinforcing film, appropriate rigidity can be imparted, so for thin components such as flexible devices, the effects of improved operability and damage prevention can be expected. In the manufacturing process of the device, when the reinforcing film is laminated to the semi-finished product, the reinforcing film can also be laminated to the semi-finished product of a large size before being cut into the product size. The reinforcing film can be laminated in a roll-to-roll manner on the mother roll of the device manufactured by the roll-to-roll process.

[0137] For example, after the reinforcement film is attached to the mother roll of the device or its semi-finished product in a roll-to-roll manner, the mother roll attached with the reinforcement film is cut and separated into individual products, and only the reinforcement film is cut by half cutting, and the reinforcement film in the non-reinforcement target area is peeled off, thereby obtaining a device with the reinforcement film attached to the reinforcement target area. The cutting method is not particularly limited, and an appropriate cutting method such as a rotary cutter, a press-in knife (such as a Thomson knife), a laser cutter, etc. can be used.

[0138] Before laminating the reinforcement film, the surface of the adherend may be subjected to activation treatment for the purpose of cleaning, etc. Examples of the surface activation treatment include plasma treatment, corona treatment, glow discharge treatment, and the like.

[0139] From the viewpoint of easy peeling from the adherend and preventing residual adhesive on the adherend after peeling the reinforcing film, the adhesive force (initial adhesive force) between the adhesive layer 2 and the adherend before photocuring is preferably 0.6N / 25mm or less, more preferably 0.5N / 25mm or less, further preferably 0.4N / 25mm or less, and may also be 0.3N / 25mm or less, 0.25N / 25mm or less, or 0.2N / 25mm or less. From the viewpoint of preventing peeling of the reinforcing film during storage and handling, the adhesive force between the adhesive layer 2 and the adherend before photocuring is preferably 0.005N / 25mm or more, and more preferably 0.01N / 25mm or more.

[0140] The adhesive strength was determined by a peel test using a polyimide film as the adherend, a tensile speed of 300 mm / min, and a peeling angle of 180°. Unless otherwise specified, the adhesive strength is a measured value at 25°C. The adhesive strength between the adhesive layer before photocuring and the adherend was measured using a sample that was left to stand at 25°C for 30 minutes after bonding.

[0141] The shear storage elastic modulus (hereinafter referred to as "storage elastic modulus") of the adhesive layer 2 before photocuring at a temperature of 25°C is preferably 15 kPa or more, more preferably 20 kPa or more, and may be 25 kPa or more or 30 kPa or more. The larger the storage elastic modulus of the adhesive layer before photocuring at room temperature, the better the cutting processability, and there is a tendency that the residual adhesive on the adherend is suppressed when the reinforcing film is peeled off from the adherend.

[0142] On the other hand, when the storage elastic modulus of the adhesive layer at room temperature before photocuring is too large, the storage elastic modulus of the adhesive layer after photocuring also tends to increase, and sometimes the adhesion and impact resistance to the adherend are insufficient. In addition, when the storage elastic modulus of the adhesive layer before photocuring is large, the storage elastic modulus of the adhesive layer after photocuring also tends to increase. When applied to foldable devices, the adhesive layer cannot absorb the strain of the bending part and its surroundings, and the reinforcing film is easily peeled off from the device. Therefore, the storage elastic modulus of the adhesive layer before photocuring at a temperature of 25°C is preferably less than 50 kPa, more preferably less than 45 kPa, and further preferably less than 40 kPa.

[0143] The storage elastic modulus of the adhesive layer is obtained by reading the value at a predetermined temperature when measured at a frequency of 1 Hz and a temperature increase rate of 5°C / min in a range of -70 to 200°C according to the method described in JIS K7244-1 "Plastics - Test methods for dynamic mechanical properties". In this specification, the storage elastic modulus is a value at a temperature of 25°C unless otherwise specified.

[0144] After the reinforcing film is attached to the adherend, the adhesive layer 2 is irradiated with active light, thereby photocuring the adhesive layer. As the active light, ultraviolet rays are preferred. The irradiation intensity and irradiation time of the active light can be appropriately set according to the composition, thickness, etc. of the adhesive layer 2. The irradiation of the active light of the adhesive layer 2 can be implemented from any side of the film substrate 1 side and the adherend side, or the irradiation of the active light can be performed from both sides.

[0145] When the adhesive layer 2 is photocured, the photocuring agent undergoes a curing reaction, and the adhesive force to the adherend increases. From the perspective of the adhesive reliability during practical use of the device, the adhesive force F1 between the adhesive layer and the adherend after photocuring at a temperature of 25°C is preferably 3N / 25mm or more, more preferably 5N / 25mm or more, and may also be 7N / 25mm or more, 9N / 25mm or more, or 10N / 25mm or more. The adhesive force F1 between the adhesive layer and the adherend after photocuring is preferably 10 times or more of the adhesive force F0 between the adhesive layer and the adherend before photocuring, more preferably 15 times or more, further preferably 20 times or more, and may also be 30 times or more or 50 times or more.

[0146] The bonding strength F2 between the photocured adhesive layer and the adherend at a temperature of 85°C is preferably 1N / 25mm or more, more preferably 2N / 25mm or more, further preferably 3N / 25mm or more, and may also be 4N / 25mm or more, 5N / 25mm or more, or 6N / 25mm or more.

[0147] As described above, by including urethane (meth)acrylate as a photocuring agent, the cohesive force at the bonding interface is improved, and there is a tendency for the adhesive force of the pressure-sensitive adhesive layer after photocuring to increase.

[0148] From the viewpoint of achieving high adhesion to the adherend after photocuring, the storage elastic modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 40 kPa or more, more preferably 50 kPa or more, and may also be 55 kPa or more or 60 kPa or more. On the other hand, when the storage elastic modulus of the adhesive layer after photocuring is too large, there is a tendency for the adhesion and impact mitigation (cushioning) to the adherend to be reduced. In addition, when the storage elastic modulus of the adhesive layer after photocuring is too large, when applied to a foldable device, the reinforcing film is easily peeled off from the device at the bending portion and its periphery. Therefore, the storage elastic modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 100 kPa or less, more preferably 90 kPa or less, and further preferably 80 kPa or less.

[0149] There is a tendency that the storage elastic modulus of the adhesive layer after photocuring becomes smaller as the amount of crosslinking agent and the amount of photocuring agent is smaller, and there is a tendency that the increase in the storage elastic modulus of the adhesive layer caused by photocuring becomes smaller as the amount of photocuring agent is smaller. In addition, by including a multifunctional (meth)acrylate and a urethane (meth)acrylate without a urethane bond as a photocuring agent, there is a tendency to suppress the increase in the storage elastic modulus of the adhesive layer caused by photocuring and to improve the bonding strength to the adherend.

[0150] The storage elastic modulus of the adhesive layer after photocuring at a temperature of -40°C is preferably 1000 kPa or less, more preferably 900 kPa or less, and may be 800 kPa or less, 750 Pa or less, or 700 kPa or less. The smaller the storage elastic modulus at -40°C, the smaller the change in the storage elastic modulus accompanying the temperature change, and there is a tendency that the warping of the reinforcement film and the adherend to which the reinforcement film is attached after the temperature cycle test is suppressed. The storage elastic modulus of the adhesive layer after photocuring at a temperature of -40°C may be 300 kPa or more, 400 kPa or more, 450 kPa or more, or 500 kPa or more.

[0151] From the perspective of improving the adhesive strength at high temperatures and ensuring the adhesive layer's ability to follow deformation such as bending of the adherend, the storage elastic modulus of the photocured adhesive layer at a temperature of 85°C is preferably 40 to 100 kPa, more preferably 50 to 90 kPa, and can be 55 to 85 kPa or 60 to 80 kPa.

[0152] The difference between the storage elastic modulus at -40°C and the storage elastic modulus at 85°C of the adhesive layer after photocuring is preferably 900 kPa or less, more preferably 800 kPa or less, and further preferably 700 kPa or less. The storage elastic modulus at -40°C of the adhesive layer after photocuring is preferably 10 times or less of the storage elastic modulus at 85°C, more preferably 9.5 times or less, and further preferably 9 times or less. The smaller the difference between the storage elastic modulus at low temperature (-40°C) and high temperature (85°C), the more there is a tendency for the warping of the reinforcement film and the adherend to which the reinforcement film is bonded after the temperature cycle test to be suppressed.

[0153] Similar to the storage elastic modulus at room temperature (25°C), the less the amount of crosslinking agent and the less the amount of photocuring agent, the smaller the storage elastic modulus of the adhesive layer after photocuring at low temperature (-40°C) and high temperature (85°C). In addition, by including multifunctional (meth)acrylates and urethane (meth)acrylates without urethane bonds as photocuring agents, there is a tendency to suppress the increase in the storage elastic modulus of the adhesive layer after photocuring at low temperatures and to improve the adhesion to the adherend. Furthermore, the main monomer of the acrylic base polymer is (meth)acrylic acid C 6-9 Alkyl esters, other than (meth)acrylic acid C 6-9 In addition to the alkyl esters, it also contains (meth) acrylic acid C 10-20 When the alkyl ester is used as a monomer component, the temperature dependence of the storage elastic modulus of the pressure-sensitive adhesive layer after photocuring tends to be reduced.

[0154] The difference between the storage elastic modulus at 25°C and the storage elastic modulus at 85°C of the photocured adhesive layer is preferably 50 kPa or less, more preferably 30 kPa or less, further preferably 20 kPa or less, and may be 15 kPa or less, 10 kPa or less, or 5 kPa or less. The storage elastic modulus at 85°C of the photocured adhesive layer may be less than the storage elastic modulus at 25°C. The storage elastic modulus at 85°C of the photocured adhesive layer is preferably 0.8 to 1.2 times the storage elastic modulus at 25°C, more preferably 0.85 to 1.15 times, and may be 0.9 to 1.1 times, 0.93 to 1.07 times, or 0.95 to 1.05 times.

[0155] The smaller the difference between the storage elastic modulus at room temperature (25°C) and high temperature (85°C), the more there is a tendency to suppress the warping of the reinforced film and the adherend bonded with the reinforced film after the temperature cycle test. In addition, when the reinforced film is applied to a foldable device, there is a tendency to suppress the peeling of the reinforced film accompanied by deformation at the bending part (hinge part) and its vicinity. The lower the glass transition temperature of the base polymer, the more the region (stable region) with low temperature dependence of viscoelasticity shifts to low temperature, so there is a tendency to reduce the difference between the storage elastic modulus at room temperature and high temperature.

[0156] By laminating the reinforcing film, appropriate rigidity is imparted to the adherend, and stress is relieved and dispersed, thereby suppressing various troubles that may occur in the manufacturing process, improving production efficiency and yield.

[0157] The adhesive layer 2 of the reinforcement film of the present invention is photocurable, and the curing time can be set arbitrarily. Before the adhesive layer is photocured, the reinforcement film of the present invention has a low adhesive force to the adherend after surface treatment, so it is easy to peel off from the adherend, and even in the case of lamination or poor lamination, reprocessing is also easy. In addition, processing such as selectively removing the reinforcement film from the non-reinforcement target area is also easy.

[0158] After the adhesive layer is photocured, it exhibits high adhesive force to the adherend, so the reinforcement film is not easy to peel off from the device surface. In a device with a reinforcement film in which the reinforcement film of the present invention is attached to a flexible device using a resin substrate, the reinforcement film is not easy to peel off at the bent part even in the case of repeated bending. In addition, the change in the storage elastic modulus of the adhesive layer accompanying temperature changes is small, so the warping of the device can be suppressed, the display characteristics can be maintained, and the reinforcement film is not easy to peel off accompanying temperature changes, and the reliability is excellent.

[0159] [Example]

[0160] The present invention will be further described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0161] [Preparation of base polymer]

[0162] <Polymer A>

[0163] In a reaction vessel equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet pipe, 20 parts by weight of butyl acrylate (BA), 70 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of lauryl acrylate (LA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA) and 1 part by weight of N-vinyl-2-pyrrolidone (NVP) as monomers, 0.1 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent were added, and nitrogen was introduced and nitrogen replacement was performed for about 1 hour while stirring. Then, the mixture was heated to 60°C and reacted for 7 hours to obtain a solution of acrylic polymer A with a weight average molecular weight of 1.8 million.

[0164] <Polymers B to D>

[0165] The amount of monomers charged was changed as shown in Table 1, and the amount of the thermal polymerization initiator (AIBN) was changed to 0.2 parts by weight in the polymerization of polymers B and D. Except for these changes, the polymerization of polymer A was carried out in the same manner as in the polymerization to obtain solutions of polymers B to D.

[0166] The monomer ratios charged in acrylic polymers A to D and the weight average molecular weight (Mw) of the polymers are listed in Table 1. The weight average molecular weight (polystyrene equivalent) was measured using GPC ("HLC-8220GPC" manufactured by Tosoh Corporation) under the following conditions.

[0167] Sample concentration: 0.2 wt% (tetrahydrofuran solution).

[0168] Sample injection volume: 10 μL.

[0169] Eluent: THF (tetrahydrofuran).

[0170] Flow rate: 0.6 mL / min.

[0171] Measurement temperature: 40℃.

[0172] Sample column: TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns).

[0173] Reference column: TSKgel SuperH-RC (1 column).

[0174] In Table 1, monomers are described by the following abbreviations.

[0175] BA: Butyl acrylate.

[0176] 2EHA: 2-ethylhexyl acrylate.

[0177] NOAA: n-octyl acrylate.

[0178] LA: Lauryl acrylate.

[0179] 2HEA: 2-Hydroxyethyl acrylate.

[0180] 4HBA: 4-Hydroxybutyl acrylate.

[0181] AA: Acrylic acid.

[0182] NVP: N-vinyl-2-pyrrolidone.

[0183] [Table 1]

[0184]

[0185] [Production of reinforcement film]

[0186] <Preparation of Adhesive Composition>

[0187] A crosslinking agent, a multifunctional acrylate (having no urethane bond) and a urethane acrylate as a photocuring agent, and a photopolymerization initiator were added to the acrylic polymer solution and uniformly mixed to prepare an adhesive composition shown in Table 2.

[0188] As a photopolymerization initiator, 0.3 parts by weight of "Omnirad 651" manufactured by IGM Resins was added to 100 parts by weight of the solid content of the acrylic polymer. The crosslinking agent and the photocuring agent (multifunctional acrylate and urethane acrylate) were added in the amounts shown in Table 2. The addition amounts in Table 2 are amounts (parts by weight of the solid content) relative to 100 parts by weight of the acrylic polymer. The details of the crosslinking agent and the photocuring agent are as follows.

[0189] (Crosslinking agent)

[0190] C / HX: isocyanurate of hexamethylene diisocyanate ("CORONATE HX" manufactured by Tosoh Corporation).

[0191] T / C: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (tetrafunctional epoxy compound, "TETRAD C" manufactured by Mitsubishi Gas Chemical).

[0192] (Multifunctional acrylate)

[0193] A200: "NK ester A200" manufactured by Shin-Nakamura Chemical Industry Co., Ltd. (polyethylene glycol #200 (n=4) diacrylate; molecular weight 308, functional group equivalent 154 g / eq).

[0194] M350: trimethylolpropane EO-modified (n=1) triacrylate ("ARONIX M-350" manufactured by Toagosei Co., Ltd., functional group equivalent: 143 g / eq).

[0195] ADPHE: ethoxylated dipentaerythritol polyacrylate ("NK ester A-DPH-12E" manufactured by Shin-Nakamura Chemical Industry Co., Ltd., functional group equivalent weight: about 200 g / eq).

[0196] (Urethane Acrylate)

[0197] UA306: Pentaerythritol triacrylate-toluene diisocyanate adduct ("UA-306T" manufactured by Kyoeisha Chemical, functional group equivalent: 128 g / eq).

[0198] UA510: dipentaerythritol pentaacrylate hexamethylene diisocyanate adduct ("UA-510H" manufactured by Kyoeisha Chemical, functional group equivalent: 181 g / eq).

[0199] UF-X9-83: Urethane acrylate having a polycarbonate skeleton ("UF-X9-83" manufactured by Kyoeisha Chemical, number of functional groups: 2 to 3, weight average molecular weight: 8400).

[0200] <Application and cross-linking of adhesive solution>

[0201] The adhesive composition was applied to a 50 μm thick polyethylene terephthalate film substrate ("DIAFOILT100" manufactured by Mitsubishi Chemical) without surface treatment using a fountain roll to a thickness of 15 μm after drying. After drying at 130°C for 1 minute to remove the solvent, the release-treated surface of a release liner (a 25 μm thick polyethylene terephthalate film with a silicone release treatment on the surface) was attached to the applied surface of the adhesive. Then, an aging treatment was performed for 4 days in an atmosphere of 25°C, and cross-linking was performed to obtain a reinforced film having an adhesive sheet laminated on the film substrate and a release liner temporarily fixed thereon.

[0202] [evaluate]

[0203] <Adhesion to polyimide film>

[0204] (Adhesive Strength of Adhesive Layer Before Photocuring)

[0205] A 25 μm thick polyimide film (UBE "UPILEX25S") was attached to a glass plate via a double-sided adhesive tape (Nitto Denko "No.531") to obtain a polyimide film substrate for measurement. The release liner was peeled off from the surface of a reinforcement film cut into a size of 25 mm wide x 100 mm long and attached to the polyimide film substrate for measurement using a hand roller.

[0206] After the sample was left to stand at 25° C. for 30 minutes, the edge of the film substrate of the reinforcement film was held with a chuck and a 180° peel test was performed at a tensile speed of 300 mm / min to measure the peel strength (adhesion force F0 of the reinforcement film to the polyimide film).

[0207] (Adhesion strength of adhesive layer after photocuring)

[0208] After bonding the reinforcement film to the polyimide film substrate for measurement, the film was irradiated from the reinforcement film side (film substrate side) using an LED light source with a wavelength of 365 nm to a cumulative light intensity of 4000 mJ / cm 2 The adhesive layer was photocured by ultraviolet light. The test sample was used to measure the adhesive force F1 based on the 180° peel test at a temperature of 25°C in the same manner as above. Furthermore, the test sample after the adhesive layer was photocured was stored in an oven at a temperature of 85°C for 5 minutes, and then a 180° peel test was performed in an environment at a temperature of 85°C to measure the adhesive force F2.

[0209] <Storage elastic modulus>

[0210] On the release liner, the adhesive composition was coated and cross-linked in the same manner as above to prepare an adhesive sheet (before photocuring). A release liner was attached to the surface of the adhesive layer of the adhesive sheet before photocuring, oxygen was blocked, and irradiated with a 365nm LED lamp at 4000mJ / cm 2 The adhesive sheet before and after photocuring were laminated to prepare a test sample with a thickness of about 1.5 mm. The dynamic viscoelasticity was measured using a rotational rheometer ("Discovery-HR2" manufactured by TA Instruments) under the following conditions, and the shear storage elastic modulus G' values ​​were read at -40°C, 25°C, and 85°C.

[0211] (Measurement conditions)

[0212] Deformation mode: twist.

[0213] Measuring frequency: 1Hz.

[0214] Heating rate: 5°C / min.

[0215] Measuring temperature: -70~200℃.

[0216] Shape: Parallel Plate

[0217] <Temperature cycle test>

[0218] The release liner was peeled off from the surface of the reinforcement film, and the film was laminated to a 25 μm thick polyimide film ("UPILEX 25S" manufactured by UBE) using a hand roller. The film was then irradiated from the reinforcement film side (film substrate side) using an LED light source with a wavelength of 365 nm to a cumulative light intensity of 4000 mJ / cm 2 The adhesive layer is photocured by ultraviolet rays. The test sample is cut into a size of 20mm×100mm and subjected to a temperature cycle test. Regarding the temperature cycle, after the sample is introduced into the test tank, it is kept at -40°C for 30 minutes, heated to 85°C (6.25°C / minute), kept at 85°C for 30 minutes and cooled to -40°C (6.25°C / minute) as one cycle, and 200 cycles are performed. The sample after the temperature cycle test is placed on a horizontal table with the long sides in contact, and the curling amount at the end is measured.

[0219] <Adherent contamination>

[0220] The release liner was peeled off from the surface of the reinforcement film cut into 25 mm wide x 100 mm long, and the film was attached to the polyimide film substrate for measurement using a hand roller. After standing at 25°C for 30 minutes or 24 hours, the reinforcement film was peeled off from the polyimide film, and the surface of the polyimide film was visually observed under a fluorescent lamp to confirm whether there was contamination. The contamination of the adherend was evaluated according to the following criteria.

[0221] A: No contamination was observed in the sample peeled off after being left to stand for 24 hours.

[0222] B: Contamination was observed in the sample peeled off after standing for 24 hours, but no contamination was observed in the sample peeled off after standing for 30 minutes.

[0223] C: Contamination was observed in the sample peeled off after being left to stand for 30 minutes.

[0224] Table 2 shows the composition of the binder of each reinforcement film (the type of base polymer, the amount of crosslinking agent added, the type and amount of photocuring agent added) and the evaluation results.

[0225] [Table 2]

[0226]

[0227] In Comparative Example 1, which used an adhesive composition containing 2 parts by weight of a multifunctional acrylate (M350) as a photocuring agent relative to 100 parts by weight of polymer A, the adhesive force F0 to the polyimide film exceeded about 1 N / 25 mm, showing a large initial adhesive force. Comparative Example 2, which contained 0.15 parts by weight of a urethane acrylate (UA306) as a photocuring agent, showed a larger initial adhesive force than Comparative Example 1.

[0228] In Example 1, which contains 2 parts by weight of multifunctional acrylate (M350) and 0.15 parts by weight of urethane acrylate (UA306) as a photocuring agent relative to 100 parts by weight of polymer A, the initial adhesive force F0 is smaller than that of Comparative Examples 1 and 2, and the adhesive force after photocuring is larger. In addition, in Example 1, the storage elastic modulus of the adhesive after photocuring is less than 60 kPa, and has flexibility suitable for foldable devices, etc.

[0229] In Examples 2 to 4 in which the amount of multifunctional acrylate was increased compared to Example 1, it was observed that the larger the amount of multifunctional acrylate, the smaller the initial adhesive force F0 and the larger the adhesive force F1 after photocuring. On the other hand, in Example 5 in which the amount of multifunctional acrylate was further increased than that of Example 4, the adhesive force after photocuring was smaller than that of Example 4. In Comparative Example 3 in which the amount of multifunctional acrylate was further increased, the adhesive force after photocuring was further reduced. In addition, in Comparative Example 3, when the reinforcing film was peeled off before photocuring of the adhesive, contamination of the adherend was observed.

[0230] In Examples 1 to 5 and Comparative Example 3, as the amount of multifunctional acrylate increases, the storage elastic modulus of the adhesive layer before photocuring tends to decrease, while the storage elastic modulus of the adhesive after photocuring tends to increase, and the storage elastic modulus at low temperature (-40°C) increases significantly. As the storage elastic modulus of the adhesive layer after photocuring increases at low temperatures, the difference between the storage elastic modulus at low temperatures (-40°C) and high temperatures (85°C) increases, and a tendency for the curling of the sample after the temperature cycle test to increase is observed.

[0231] In Examples 14 and 15, in which the type of multifunctional acrylate was changed, the initial adhesive force F0 to the adherend was small, and the adhesive force F2 of the adhesive layer at high temperature after photocuring showed a large value, similar to Example 4. The curling amount of the sample after the temperature cycle test of Example 15 was the same as that of Example 4. In Example 14 using a bifunctional acrylate (A200), the storage elastic modulus at each temperature was smaller than that of Examples 4 and 15, and the curling of the sample after the temperature cycle test was reduced.

[0232] Examples 6 to 8, in which the amount of urethane acrylate was increased compared to Example 4, were similar to Example 4 in that the initial adhesive force F0 to the adherend was small, the adhesive force F2 at high temperature of the photocured adhesive layer was large, and the storage elastic modulus was low, and the curling of the sample after the temperature cycle test was reduced. In Examples 6 to 8, a tendency was observed that the adhesive force F2 at high temperature increased with the increase in the amount of urethane acrylate. In addition, a tendency was observed that the storage elastic modulus of the photocured adhesive layer increased with the increase in the amount of urethane acrylate, but the increase in the storage elastic modulus was small, and no difference was observed in the curling amount of the sample after the temperature cycle test.

[0233] In Examples 12 and 13 using urethane acrylates different from that in Example 4, the initial adhesive force F0 was small, and the adhesive force F2 at high temperature of the pressure-sensitive adhesive layer after photocuring showed a large value, similarly to Example 4.

[0234] In Example 12 using 10-functional urethane acrylate (UA510), the initial adhesive force F0 is smaller than that in Example 4 using 6-functional urethane acrylate (UA306), and the adhesive force F2 at high temperature after photocuring is greater than that in Example 4. On the other hand, in Example 13 using high molecular weight urethane acrylate (UF-X9-83), F0 becomes larger and F2 becomes smaller than that in Examples 4 and 12. From these results, it can be seen that the more functional groups of urethane acrylate and the smaller the functional group equivalent, the greater the effect of reducing the initial adhesive force and improving the adhesive force.

[0235] By comparing Example 1 with Examples 9 to 11, it was observed that the greater the amount of cross-linking agent, the smaller the adhesion of the adhesive layer before and after photocuring, and the larger the storage elastic modulus. It was observed that the curling amount of the sample after the temperature cycle test tended to increase with the increase of the storage elastic modulus.

[0236] In Comparative Example 4, which uses polymer B having a composition of 2EHA / 2HEA=96 / 4 as the base polymer of the adhesive, the adhesive force F2 of the adhesive layer after photocuring at high temperature becomes smaller than that of Example 4. In addition, in Comparative Example 4, the storage elastic modulus of the adhesive layer after photocuring at low temperature is large, and the difference between the storage elastic modulus at low temperature and high temperature (85°C) is large, so the curling of the sample after the temperature cycle test becomes large.

[0237] In Comparative Example 4, which uses polymer B having a composition of 2EHA / 2HEA=96 / 4 as the base polymer of the adhesive, the adhesive force F2 of the adhesive layer after photocuring at high temperature becomes smaller than that of Example 4. In addition, in Comparative Example 4, the storage elastic modulus of the adhesive layer after photocuring at low temperature is large, and the difference between the storage elastic modulus at low temperature and high temperature (85°C) is large, and the curling of the sample after the temperature cycle test becomes large.

[0238] Comparative Example 5 using polymer C having a composition of BA / NOAA / 4HBA=20 / 70 / 10 as the base polymer of the adhesive shows a smaller value of the adhesive force F2 at high temperature than Comparative Example 4. In addition, the storage elastic modulus at low temperature of the adhesive layer after photocuring in Comparative Example 5 is smaller than that in Comparative Example 4, but the storage elastic modulus at low temperature and the difference between the storage elastic modulus at low temperature and high temperature are larger than those in Example 4, and the curl of the sample after the temperature cycle test is also larger than that in Example 1.

[0239] In Comparative Example 6, in which polymer D having a composition of BA / AA=95 / 5 was used as the base polymer of the adhesive and the amount of the multifunctional acrylate was 30 parts by weight, the adhesive force F2 of the adhesive layer at high temperature after photocuring was small and the curl of the sample after the temperature cycle test was large.

[0240] From these results, it can be seen that by using the 12 The polymer A of alkyl ester lauryl acrylate is used as the monomer component of the base polymer, and a multifunctional (meth)acrylate without a urethane bond and a urethane (meth)acrylate are used in combination as a photocuring agent. The adhesive layer after photocuring can have both high adhesion at high temperatures and reduced curling during temperature cycling due to a low storage elastic modulus.

Claims

1. A reinforcement film comprising a film substrate and an adhesive layer fixedly laminated on one main surface of the film substrate, wherein: The adhesive layer is formed of a photocurable composition, the photocurable composition comprising an acrylic base polymer, a photocuring agent having two or more photopolymerizable functional groups, and a photopolymerization initiator. The acrylic base polymer comprises a (meth)acrylic acid having an alkyl group with 6 to 9 carbon atoms. 6-9 Alkyl esters, (meth)acrylic acid C wherein the alkyl group has 10 to 20 carbon atoms 10-20 alkyl ester, and one or more selected from the group consisting of a hydroxyl group-containing monomer and a carboxyl group-containing monomer as monomer components, with respect to 100 parts by weight of the total amount of the monomer components, (meth)acrylic acid C 6-9 The amount of alkyl ester is 40 parts by weight or more, The acrylic base polymer has a cross-linked structure. The photocurable composition includes 2 to 25 parts by weight of a polyfunctional (meth)acrylate having no urethane bond as the photocuring agent based on 100 parts by weight of the acrylic base polymer, and 0.03 to 5 parts by weight of a urethane (meth)acrylate as the photocuring agent based on 100 parts by weight of the acrylic base polymer.

2. The enhanced film according to claim 1, wherein: The acrylic base polymer has a crosslinked structure introduced therein using 0.05 to 1.0 parts by weight of a crosslinking agent based on 100 parts by weight of the polymer.

3. The enhanced film according to claim 2, wherein: The crosslinking agent is an isocyanate crosslinking agent or an epoxy crosslinking agent.

4. The enhanced film according to claim 1, wherein: With respect to 100 parts by weight of the total monomer components of the acrylic base polymer, (meth)acrylic acid C 10-20 The amount of the alkyl ester is 1 to 40 parts by weight.

5. The enhanced film according to claim 1, wherein The functional group equivalent of the (meth)acryloyl group of the multifunctional (meth)acrylate is 80 to 500 g / eq.

6. The enhanced film according to claim 1, wherein The functional group equivalent of the (meth)acryloyl group of the urethane (meth)acrylate is 80 to 5000 g / eq.

7. The enhanced film according to claim 1, wherein: The urethane (meth)acrylate has four or more (meth)acryloyl groups in one molecule.

8. The reinforced film according to any one of claims 1 to 7, wherein The adhesive layer has an adhesive force F0 of 0.6 N / 25 mm or less at a temperature of 25° C. to the polyimide film before photocuring. The adhesive layer has an adhesive force F1 of 3.0 N / 25 mm or more at a temperature of 25° C. to the polyimide film after photocuring, and an adhesive force F2 of 1.0 N / 25 mm or more at a temperature of 85° C. to the polyimide film after photocuring.

9. The reinforced film according to any one of claims 1 to 7, wherein The adhesive layer has a shear storage elastic modulus of 100 kPa or less at a temperature of 25° C. after photocuring.

10. The reinforced film according to any one of claims 1 to 7, wherein The adhesive layer has a shear storage elastic modulus of 1000 kPa or less at a temperature of -40°C after photocuring.

11. A method for manufacturing a device, which is a method for manufacturing a device having a reinforcement film attached to the surface, wherein: After temporarily fixing the adhesive layer of the reinforcement film according to any one of claims 1 to 10 to the surface of an adherend, The adhesive layer is irradiated with active light rays to photo-cure the adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.

12. The method for manufacturing a device according to claim 11, wherein: After the reinforcement film is temporarily fixed to the adherend, before the adhesive layer is photocured, the reinforcement film temporarily fixed to the adherend is cut to peel and remove the reinforcement film from a partial region on the adherend.

13. The method for manufacturing a device according to claim 11 or 12, wherein: The adherend is a bendable image display element.

14. A reinforcement method, which is a reinforcement method of laminating a reinforcement film on the surface of an adherend, wherein: The adhesive layer of the reinforcement film according to any one of claims 1 to 10 is temporarily fixed to the surface of the adherend, The adhesive layer is irradiated with active light rays to photo-cure the adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.

Citation Information

Patent Citations

  • Reinforcing film, device with reinforcing film, and method for manufacturing the same

    WO2022050009A1